Analisis faktor risiko terjadinya picky eater pada balita (2-5 tahun) di Desa Sumuradem, Kecamatan Sukra, Kabupaten Indramayu - Mutiara Hikmah Aprilia; Muhammad Duddy Satrianugraha Wahidin; Imam Syakhruddin (UHAMKA PRESS, 2026)
Picky eating is a common eating behavior problem in toddlers that can affect their nutritional status and growth. This condition is influenced by maternal characteristics and parenting patterns. This study aims to examine the effects of parity, maternal occupation, exclusive breastfeeding, complementary feeding (MP-ASI), gadget use, and sensory sensitivity on picky eating among children aged 2–5 years. A quantitative study with a cross-sectional design was conducted involving 93 mothers with children aged 2–5 years who attended the Posyandu in Sumuradem Village, Sukra District, Indramayu. Data were analyzed using the Chi-Square test with a significance level of 0.05. Significant factors associated with picky eating were parity (p=0.001), maternal occupation (p=0.006), complementary feeding (MP-ASI) (p=0.023), gadget use (p=0.002), and exclusive breastfeeding (p=0.011). Sensory sensitivity showed no significant effect (p=0.935). The most dominant factor was parity, followed by maternal occupation and complementary feeding. Parity, maternal occupation, and complementary feeding are the main factors influencing picky eating among toddlers aged 2–5 years. Promotive and preventive interventions should focus on improving maternal knowledge of child feeding and providing policy support for working mothers.